2012
DOI: 10.1158/1078-0432.ccr-12-0891
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Radiosensitivity Molecular Signature in Breast Cancer

Abstract: Purpose Previously, we developed a radiosensitivity molecular signature (RSI) that was clinically-validated in three independent datasets (rectal, esophageal, head and neck) in 118 patients. Here, we test RSI in radiotherapy (RT) treated breast cancer patients. Experimental Design RSI was tested in two previously published breast cancer datasets. Patients were treated at the Karolinska University Hospital (n=159) and Erasmus Medical Center (n=344). RSI was applied as previously described. Results We tested… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
168
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(170 citation statements)
references
References 42 publications
1
168
0
1
Order By: Relevance
“…Previous attempts to identify radiation-specific signatures to predict likelihood of benefit to adjuvant radiotherapy have either failed independent validation or have not been disease-specific resulting in inconsistent performance in independent cohorts (8)(9)(10)(11)(12). A recent study demonstrated the feasibility of this approach in the postmastectomy setting using patient-derived gene expression data from the DBCG82bc trials (13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to identify radiation-specific signatures to predict likelihood of benefit to adjuvant radiotherapy have either failed independent validation or have not been disease-specific resulting in inconsistent performance in independent cohorts (8)(9)(10)(11)(12). A recent study demonstrated the feasibility of this approach in the postmastectomy setting using patient-derived gene expression data from the DBCG82bc trials (13).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple gene signatures associated with radiosensitivity have been described (11,12), but clinical models able to detect single gene variants associated with radiation response have not been validated. In the case of NSCLC, determination of local control rates for thoracic tumors are confounded by variations in multiple treatment factors including dose, tumor size, planning techniques, respiratory motion, the uncertainty of computed tomography-based target definition, and the interactive effects of systemically delivered therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed a multigene expression model of tumor radiosensitivity [14]. This model has been validated in multiple independent clinical cohorts including breast, rectal, esophageal, and head and neck cancers [14,15]. This model predicts a radiosensitivity index (RSI) that is directly proportional to tumor radioresistance, (RSI, high index = radioresistance).…”
Section: Introductionmentioning
confidence: 99%